2012
DOI: 10.5539/ijel.v2n1p257
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sentence Making, Composition Writing and Cloze Test Assignments on Vocabulary Learning of Pre-intermediate EFL Students

Abstract: This study aimed to investigate the effects of three writing assignments (sentence making, composition writing and cloze test) on vocabulary learning and tried to compare the effectiveness of these assignments to see which one has the best effect. Accordingly, 102 homogeneous pre-intermediate EFL female learners, studying English at an institute in Shiraz, Iran, were randomly divided into three groups. At the beginning, an unannounced researcher-made pre-test including 60 multiple choice tests (60 vocabulary i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
2
4
1
Order By: Relevance
“…The mentioned finding is in line with Brame and Biel (2015), Chehrazad and Ajideh (2012), Talebzadeh and Bagheri (2012), and Zarei and Neya (2014), but it is a rather sharp contrast with Loch (2010). Talebzadeh and Bagheri (2012) reported a positive washback effect of cloze tests on students' vocabulary learning.…”
Section: Research Question Onesupporting
confidence: 78%
See 1 more Smart Citation
“…The mentioned finding is in line with Brame and Biel (2015), Chehrazad and Ajideh (2012), Talebzadeh and Bagheri (2012), and Zarei and Neya (2014), but it is a rather sharp contrast with Loch (2010). Talebzadeh and Bagheri (2012) reported a positive washback effect of cloze tests on students' vocabulary learning.…”
Section: Research Question Onesupporting
confidence: 78%
“…The mentioned finding is in line with Brame and Biel (2015), Chehrazad and Ajideh (2012), Talebzadeh and Bagheri (2012), and Zarei and Neya (2014), but it is a rather sharp contrast with Loch (2010). Talebzadeh and Bagheri (2012) reported a positive washback effect of cloze tests on students' vocabulary learning. Brame and Biel (2015) declared that various testing format can enhance learning and they suggested that feedback on tests would enhance the beneficial positive washback effects of tests.…”
Section: Research Question Onesupporting
confidence: 78%
“…The mentioned finding is in line with Brame and Biel (2015), Chehrazad and Ajideh (2012), Ko, (2010), Kro mann et al (2009), Taleb zadeh and Bagheri (2012), Zarei and Neya, (2014), but it is a rather sharp contrast with Loch (2010). Talebzadeh and Bagheri (2012) reported a positive washback effect of clo ze tests on students' vocabulary learning. Brame and Biel (2015) declared that various testing format can enhance learning and they suggested that feedback on tests would enhance the beneficial positive washback effects of tests.…”
Section: Discussionmentioning
confidence: 98%
“…It was also concluded that the effectiveness of the provision of example sentences to target words and items in learning activity is more prominent when learners make their own example sentences than when the sentences are randomly provided by the teacher in ESL and EFL contexts. Talebzadeh and Bagheri (2012) investigated the effectiveness of three writing assignments, involving sentence making, composition writing, and cloze test, on EFL learners' achievement in L2 lexical items. It was shown that the three modes of target word instruction made significant differences in the learners' knowledge of lexical items, but the sentence-making task was the least effective of the other techniques.…”
Section: Empirical Studies On Test Types Practice With a Focus On Lexical Items And Chunksmentioning
confidence: 99%